MICROBIOLOGICAL AND PHYSICOCHEMICAL QUALITY OF CURD CHESSE SOLD IN THE STATE OF ALAGOAS (BRAZIL) - SOARES, KARLA DANIELLE ALMEIDA; RAMALHO, AYODHYA CARDOSO; SALGADO, SILVANA MAGALHÃES; LIVERA, ALDA VERÔNICA SOUZA; MOTA, RINALDO APARECIDO; LEMSADDER, ABDELHAK; LEMSADDER, TERESA SEMEDO; DE MEDEIROS, ELIZABETH SAMPAIO (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2013)
The present study aimed to evaluate the microbiological and physicochemical quality of curd cheese commercialized in Alagoas (BRAZIL). Thirty samples were collect during a five months period in six points of sale. It was estimated the number of coagulase-positive Staphylococcus and coliforms, as well as the presence of Salmonella spp. and Listeria monocytogenes. Regarding physicochemical characteristics, pH, fat content and humidity were evaluated. Among the thirty analyzed samples, 20 (66.6%) were in accordance with Brazilian legislation parameters for coliforms, while 10 (33.3%) surpassed those limits. For coagulase-positive Staphylococcus 15 samples (50%) showed values above the allowed by legislation. None of the samples analyzed harbored Salmonella spp. or Listeria monocytogenes. Regarding physicochemical parameters, the average values observed were of 5.89 for pH, 23.6% for fat content and 46.96 g/100 g for humidity. Overall, the results obtained reflect the poor hygienic conditions observed from manufacture to commercialization, pointing towards a potential health risk for curd cheese consumers. Furthermore is necessary to regulate physicochemical standards for curd cheese fabication.